88 Profiling Clinical Frailty in Older Adults in an Irish Post-Acute Care Ortho-Geriatric Unit. (16th September 2019) - McDaid, Edel; Ross, Elaine; Cogan, Lisa
Abstract: Background: Clinical frailty upon admission to acute care has been shown to independently predict adverse discharge destination in geriatric patients (1). However, the prevalence of clinical frailty in post-acute care and its impact on length of stay and discharge destination has not been explored to date (2). The aims of this study were to measure clinical frailty upon admission and discharge to a post-acute Ortho-geriatric Unit (OGU) and identify its impact on length of stay (LOS) and discharge destination. Methods: A retrospective data analysis was completed of all patients admitted and discharged within a 6-month period. All received routine Multidisciplinary team (MDT) rehabilitation care. Clinical Frailty was assessed within first week of admission and the week prior to discharge using the Clinical Frailty Scale (CFS). Data was analysed using Microsoft Excel. Results: Fifty-four patients were admitted over the 6-month period. All were female, mean age 81 years and over half (55%) had a primary diagnosis of hip fracture (n=30). All were deemed frail on admission (CFS score >5). The Mild to Moderate (CFS 5 and CFS 6) Group (n=36) had a mean age 81.1 years, mean LOS 38.75 days, 96.6% independently mobile on discharge and 97.2% discharged home. The Severe (CFS 7 and CFS 8) Group (n=18) had a mean age 85.2 years, mean LOS 85.2 days, 59.4% independently mobile on discharge and 83.3%% discharged home. 75% (n=3) of patients that transitioned to long-term care were in the Severe Group. At discharge 54% of the total participants were deemed frail(CFS>5), 46% less compared to admission scores. Conclusion: All admissions to OGU were frail. MDT rehabilitation reduced frailty levels for the majority of subjects' in this study. Higher admission CFS scores resulted in increased LOS and a trend towards long-term care transition. Further research is warranted to evaluate the efficacy of CFS in post-acute geriatric population.